Factors That Influence the Capital Structure of the Mining Company (Empirical Study Company In BEI) - Mauidhotin, Kartika Hendra Titisari & Siti Nurlaela (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aims to examine the effect of sales growth, profitability, liquidity andasset structure on capital structure in mining companies listed on Indonesia StockExchange period 2012-2016. The population used in this study is all miningcompanies listed on the Indonesia Stock Exchange 7 companies. Based onsampling technique with purposive sampling method, 75 samples were obtained forfive periods; the data analysis technique used was multiple linear regressionanalysis. The result of hypothesis testing shows the variables of sales growth,profitability, and liquidity have an effect on capital structure, while asset structurevariable has no effect to capital structure. When viewed from the significance ofthe results of this study indicates that (1) there are variables sales growth,profitability, liquidity that have significant (2) only asset structure variable that hasno significant effect on capital structure (3) model used is feasible is variable salesgrowth, profitability , liquidity, and asset structure.Keywords: GROWTH, ROA, ROE, AS and DER